THE ROLE OF MARKETING MANAGEMENT IN ENHANCING THE COMPETITIVENESS OF SMALL BUSINESS ENTITIES - Vakhabov Asadullo Ubaydullo ogli (Modern American Journals, 2025)
The article examines the role of marketing management in ensuring the competitiveness of small businesses. The main problems faced by small businesses in a competitive environment are identified, and recommendations for overcoming them are proposed. The results of the study emphasize the importance of a strategic approach to marketing management for the long-term sustainable development of small enterprises.
Keywords: marketing management, small business, competitiveness, marketing strategy, digital marketing, personalization, customer experience, sustainable development.